Food Traceability in Europe, the US and China: Comparative Law and Regulatory Technology (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The issue of traceability in the food sector lies within the framework of a multiplicity of principles ranging from product identification to data recording, information integration, and accessibility. Traceability responds to a recent need for market and consumer protection which has driven and is still driving policies of major world powers in the food industry and beyond such as the European Union, the United States of America and the People’s Republic of China. In a comparative and multidisciplinary perspective, food regulation poses scientific, economic, legal and technological challenges. Thus, on the one hand, food regulation builds upon the concepts of coexistence, right to know, and precautionary principle. On the other hand, innovation through emerging technologies such as blockchain foreshadows new organizational and regulatory models for a more effective management of traceability systems within the food supply chain.
Keywords: Food regulation; Traceability; GMOs; RegTech; Blockchain